Kekerabatan Zeylanicobdella arugamensis pada Ikan Kerapu Cantang dengan Pendekatan Molekuler di Jawa Timur dan Lombok - Ochtavia, Sherly; Mahasri, Gunanti; Mufasirin, Mufasirin (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Giant grouper is a highly sought-after cultivated fish in Indonesia due to its high market value. One of the challenges in grouper aquaculture is the infestation of the sea leech ektoparasite Zeylanicobdella arugamensis. The prevalence rate of ektoparasite infestation reaches up to 100%. An effective method to manage ektoparasite infestation is through molecular profiling, serving as preliminary literature in the development of molecular biology efforts to overcome cultivation challenges in giant grouper. This research aims to study the homology and relationship of Zeylanicobdella arugamensis on giant grouper in East Java, specifically in Lamongan, Mandangin, Situbondo, and Lombok. The method used is RT-PCR with mtDNA COI gene primers. Molecular sequence data were collected from samples and compared with data from NCBI GenBank, and analyzed using Neighbor-joining phylogenetic tree method and homology data analysis on BLAST. The research results indicate clinical symptoms in giant grouper including swelling, lesions/wounds, pale skin, decreased appetite, and fin erosion. Electrophoresis results from PCR products show a single band at 750bp for samples from Lamongan, Situbondo, Mandangin, and Lombok. DNA sequencing results on NCBI BLAST and homology analysis against the reference gene were conducted. Homology analysis results between samples from Situbondo and Lamongan show the highest similarity at 98.28%, whereas the lowest similarity is between samples from Mandangin and Situbondo at 88.51%. Based on phylogenetic tree analysis, samples from Lamongan and Situbondo waters show a close relationship with a genetic distance of 0.009272.